2021
DOI: 10.1038/s41598-021-95278-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tl(III) complexes containing pyridine-2,6-dicarboxylate derivatives with selective anticancer activity through inducing mitochondria-mediated apoptosis in A375 cells

Abstract: Three novel Tl(III) complexes (C1), (C2) and (C3) were synthesized using the one-pot reactions of pyridine dicarboxylic acid derivatives, 2-aminobenzimidazole and/or 4-aminopyridine, and also thallium(III) nitrate trihydrate metal salt. The structure of all three complexes was determined by the single-crystal X-ray diffraction. C1 and C2 were realized to be isostructural with disordered square anti-prismatic geometry and for C3 arrangement of the distorted tricapped triangular prism was proposed. Cyclic voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 63 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The type of cell death induced in this cell line depicted increases in the late apoptosis pattern compared to Tl-untreated A375 cells. The suggested apoptotic pathway activated in this cell line was confirmed by western blotting assays which showed an increase in p53 protein, Bax upregulation, Bcl-2 down-regu ation, cytochrome c release, and augmented expression of procaspase-9, and 3 ( Abdolmaleki et al, 2021 ).…”
Section: Thallium and Cancermentioning
confidence: 60%
See 2 more Smart Citations
“…The type of cell death induced in this cell line depicted increases in the late apoptosis pattern compared to Tl-untreated A375 cells. The suggested apoptotic pathway activated in this cell line was confirmed by western blotting assays which showed an increase in p53 protein, Bax upregulation, Bcl-2 down-regu ation, cytochrome c release, and augmented expression of procaspase-9, and 3 ( Abdolmaleki et al, 2021 ).…”
Section: Thallium and Cancermentioning
confidence: 60%
“…Regarding the antineoplastic effects induced by Tl compounds, it seems that the ROS levels generated by the administration of this metal induce more cytotoxic effects in neoplastic cells than in normal cells, suggesting that the cellular levels of ROS play a crucial role in inducing cancer cell death. Finally, it has been demonstrated that Tl has a special affinity for cancer cells likely due to the mimicry between Tl to potassium ( Abdolmaleki et al, 2021 ; Rangel-López et al, 2022 ). Considering its biochemical and physical properties, its effects on DNA damage, and the energetic requirements of neoplastic cells future studies should focus on strategies to reduce the toxic effects of Tl and to design novel thallium-based drugs to inhibit the development and progression of several cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the cells were stained with 1 ml of JC‐1 stock solution (10 mg/ml). The assays were initiated by incubating HL60 cells with JC‐1 for 30 min at 37°C in the dark and detected using a fluorescence microscope 39 …”
Section: Methodsmentioning
confidence: 99%
“…The assays were initiated by incubating HL60 cells with JC-1 for 30 min at 37 C in the dark and detected using a fluorescence microscope. 39…”
Section: Measurement Of Mitochondrial Membrane Potentialmentioning
confidence: 99%